Measuring How Destination Image and Perceive Value Affect Customers’ Satisfaction for Ecotourism - Jaya, I Putu Gede Iwan Trisna (International Journal of Social Science and Business, 2018)
This study purpose is to determine the effect of destination image and perceived value on the satisfaction’s level of the tourists who visit ecotourism attractions. There are two studies conducted in this research, the first is to validate the effect of destination image to the customers' satisfaction level and also to see the dominant effect of each indicator from the destination image to Customer Satisfaction level. Subsequent study validates the effect of Perceived Value on the customers' satisfaction level as well as to see the dominant indicator of Perceived Value on the customers' satisfaction levels. The study population is the foreign tourists who visited Taman Ayun Pura Mengwi Badung tourist object of Bali. The samples size is set at 65 people. Respondents were selected based on convenience sampling technique from the tourists who already know that Taman Ayun Temple is an ecotourism attraction and received appreciation as world cultural heritage. The data is processed and analysed using SEM through PLS software. The results show that Destination Image and Perceived Value have a positive and significant effect on the Customers' Satisfaction. Perceived Value has a higher correlation coefficient value when it is compared to the Destination Image on the Customers' Satisfaction. This indicates that the managers of tourist object and travel should pay attention on the price paid by the tourists with acceptable or perceived benefits. Other indicators in Perceived Value that should be the evaluation's material is Functional Value and Emotional Value. This indicates that tourists who visit the tourist object pay attention to the service standard received and the pleasure feelings they obtained when they are traveling can increase the tourists' satisfaction.